KEMU’JIZATAN AL-QUR’AN - Masbukin Masbukin (An-Nida', 2012)
Al-Qur’an is verbum dei and miraculous verses that comes from the Creator of human being and the evidence of the Prophet Muhammad mission and no one able to come with the same verses even the brilliant and smart Arabian poets and it’s memorized by a lot of Muslims all over the world. Why, it’s miracle? Language, Al-Qur’an has a specific literary style which is no one can imitate even a brilliant Arabian poet and man of letters, because it has a valuable structure that is different within every Arabic language structures. It uses their language and words, but it’s not a poetry, a prose, and non a poem. Islamic Jurisdictions, Al-Qur’an is a resource of Islamic doctrine and it’s full of jurisdictions which manages the human life relation with the Creator and human beings. Islamic jurisdiction consists of faith, the principal of morals, worship, and charity. And the other side of the miracle of the al-Qur’an is the difficult signals of the science. It’s proven that al-Qur’an is absolutely not crontradicted the recent discovery based on scientific researches.